Aspects concerning the hearing of witnesses - Buzescu, Gheorghe (Technium Social Sciences Journal, 2024)
The subject matter of the present study consists of a theoretical and practical account of the modality of hearing the witness in the judicial process, also illustrated by the title of the present study, in this lecture I tried to deal with a series of theoretical and practical issues from the field of criminal procedure, criminalistics and penal, salts have been elaborated by various authors in the specialty polishes. We cannot talk about the key procedures applied to the hearing of witnesses, without knowing the criminal procedural provisions that regulate the given field, and at the same time, without knowing the personality of the witness from a psychological point of view. The conducted study deals with the well-known keys and methods regarding interviewing witnesses. Complete problems are addressed regarding witness depositions with obvious implications both in the criminal investigation phase and in the judicial sequestration phase. The given field has been subjected to numerous trials, taking into account the degree to which the criminalistic key procedures carry it, being a significant one, applied to the hearing of the witness, both from a theoretical point of view and from a practical point of view. The purpose and objectives of this work they consist in studying the mode of hearing the witness with a view to the fair settlement of the case. Achieving this goal requires solving several problems, respectively: Delimitation of the theoretical basis on the psychological process of forming witness statements; Identifying the rights and obligations of the witness; Defining the elements and types of information reception; Trying to remember the facts; Representation of the reproduction of facts; Presentation of preparation for the hearing of witnesses; Determining and clarifying theoretical approaches regarding the hearing of witnesses; Presentation of the means of recording the statements of the witness; The substantiation and highlighting of the general expectations of hearing minor witnesses; Highlighting the peculiarities of the hearing of other groups of witnesses. In the first chapter, I carried out a study on a general representation of the psychological process of training witness statements. Thus, I referred to the rights and obligations of witnesses, I related the elements and types of information reception, and I made an analysis on them. Also, we realized the resume of notions and the importance of the witness's statements, we highlighted the characteristics of the memorization of facts and of the reproduction of facts. In the second chapter, I made a study on the preparation procedures for the hearing of the witnesses and I related the key of the hearing of the witnesses, and in the last paragraph of this chapter I presented the means of recording the statements of the witness. In the third chapter, I performed an analysis of the general expectations of the hearing of minor witnesses and the particularities of the hearing of other categories of witnesses. In the end, I presented the impressions left after the study carried out, presenting at the same time different opinions, presumably also some recommendations regarding the studied field.